The Relationship Between COMT and MAO-B Gene Polymorphisms with Levodopa in Parkinson’s Disease Patients; A Review - Hasna, Vina Luthfiana; Kasasiah, Ahsanal; Manalu, Rosario Trijuliamos; Malau, Jekmal (Universitas Labuhanbatu, 2024)
Parkinson's disease is a degenerative nervous system disorder caused by the death of dopamine-producing cells in the substantia nigra. Dopaminergic treatment could alleviate motor symptoms for a period. One of the effective dopaminergic medications for symptomatic relief was Levodopa and dopamine agonists. Clinically, Levodopa was always combined with Dopa Decarboxylase (DDC) inhibitors, which redirected Levodopa metabolism towards the COMT pathway, increasing its bioavailability in the central nervous system. The purpose of this article was to investigate the relationship between COMT and MAO-B gene polymorphisms and Levodopa in Parkinson's disease patients, starting by gathering literature on the association between COMT and MAO-B polymorphisms and Levodopa in Parkinson's disease patients using various databases. Reviewed literature revealed that the most frequent polymorphism in the COMT gene was rs4680. Some polymorphisms significantly impacted the treatment of Parkinson's disease patients. However, despite efforts to identify genetic factors influencing the risk of side effects or treatment ineffectiveness, the role of pharmacogenetics in Parkinson's disease has not been fully explored and lacks consistent clinical recommendations. Further research was needed to tailor treatment to individual polymorphisms so that pharmacogenomic approaches could be applied more consistently